2012
DOI: 10.1177/0011128712461738
|View full text |Cite
|
Sign up to set email alerts
|

A Partial Test of Agnew’s General Theory of Crime and Delinquency

Abstract: In 2005, Agnew introduced a new integrated theory, which he labels a general theory of crime and delinquency. He proposes that delinquency is more likely to occur when constraints against delinquency are low and motivations for delinquency are high. In addition, he argues that constraints and motivations are influenced by variables in five life domains. Capitalizing on longitudinal data of Paternoster's Youths and Deterrence: Columbia, South Carolina, 1979-1981, a structural equation model is developed to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…That is, criminal/delinquent behavior is seen as the result of the direct effects of constraints and motivations and the indirect effects of life domains as these are mediated by constraints and motivations, though the theory also allows for some direct effects of the life domains as well. Past attempts to provide partial tests of this general theory have provided consistent, yet modest support for it (Muftic et al, 2014;Ngo & Paternoster, 2014;Ngo et al, 2011;Zhang et al, 2012). Most of these studies have tested the theory against data from adolescent samples and have either conflated constraints and motivations within life domains or neglected to include measures of either constraints or motivations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, criminal/delinquent behavior is seen as the result of the direct effects of constraints and motivations and the indirect effects of life domains as these are mediated by constraints and motivations, though the theory also allows for some direct effects of the life domains as well. Past attempts to provide partial tests of this general theory have provided consistent, yet modest support for it (Muftic et al, 2014;Ngo & Paternoster, 2014;Ngo et al, 2011;Zhang et al, 2012). Most of these studies have tested the theory against data from adolescent samples and have either conflated constraints and motivations within life domains or neglected to include measures of either constraints or motivations.…”
Section: Discussionmentioning
confidence: 99%
“…In the only test with data outside the United States, Muftic and her colleagues (2014) observed significant relationships between criminal offending and factors representing the self, family, peer, and school domains. Finally, Zhang et al (2012) were the only to test for both direct and indirect life domain effects. They observed that variables from family, peer, and school life domains had a baseline effect on self-reported delinquency among their sample of adolescents from South Carolina.…”
Section: Agnew’s General Theory Of Crimementioning
confidence: 99%
See 1 more Smart Citation
“…Aside from bivariate and multivariate results, tests of 21 interaction effects between the life domains revealed seven significant relationships, with moderate magnitudes indicated for two of these interactions. Overall, Ngo and colleagues' work suggests weak support for the theory.In contrast, findings byZhang, Day, and Cao (2012) provided greater support for the impact of life domains on delinquency. Utilizing a longitudinal sample of 1,139 juveniles from the Youths and Deterrence: Columbia,…”
mentioning
confidence: 81%
“…Agnew contends that the impact of each life domain is differentially related to an individual's stage in the life course. Subsequently, this theory may benefit from being tested with a longitudinal data set, which to date has only minimally been explored (e.g., Zhang et al 2012). Longitudinal data would allow for an exploration of both contemporaneous (this study only explored contemporaneous effects due to the cross-sectional nature of the data) and indirect lagged effects (see proposition 6); however, a minimum of three waves of data are needed (see Agnew 2005:184).…”
Section: Limitations and Future Studiesmentioning
confidence: 99%